Histone lactylation promotes multidrug resistance in hepatocellular carcinoma by forming a positive feedback loop with PTEN - Yuan Zeng; Haoran Jiang; Zhoufeng Chen; Jun Xu; Xiangting Zhang; Weimin Cai; Xianjie Zeng; Peipei Ma; Rong lin; Huilin Yu; Yuanhang He; Huiya Ying; et al. (Cell Death and Disease)
Abstract FOLFOX (5-fluorouracil, oxaliplatin, folinic acid) is a standard treatment for hepatocellular carcinoma, but its efficacy is often limited by drug resistance, the underlying mechanisms of which remain unclear. In this study, oxaliplatin (OXA)- and 5-fluorouracil (5-Fu)-resistant hepatocellular carcinoma cell lines were established, and enhanced glycolytic activity was identified in resistant cells. Inhibiting glycolysis effectively suppressed the malignant behavior of both OXA- and 5-Fu-resistant cells. Mechanistically, active glycolysis induced elevated levels of lactylation, predominantly histone lactylation, with H3K14la playing a key role in regulating gene expression. The ubiquitin E3 ligase NEDD4 was identified as a downstream target of H3K14la. Furthermore, NEDD4, regulated by histone lactylation, interacted with PTEN to mediate its ubiquitination and subsequent degradation. The downregulation of PTEN formed a positive feedback loop, further driving the malignant progression of OXA- and 5-Fu-resistant cells. This study elucidates a shared mechanism underlying OXA and 5-Fu resistance in hepatocellular carcinoma and highlights a promising therapeutic target for overcoming clinical chemotherapy resistance.